MRI assessment of the intra‐carotid route for macrophage delivery after transient cerebral ischemia. (25th June 2012) - Riou, Adrien; Chauveau, Fabien; Cho, Tae‐Hee; Marinescu, Marilena; Nataf, Serge; Nighoghossian, Norbert; Berthezène, Yves; Wiart, Marlène
Abstract : The broad aim underlying the present research was to investigate the distribution and homing of bone marrow‐derived macrophages in a rodent model of transient middle cerebral artery occlusion using MRI and ultrasmall superparamagnetic iron oxide (USPIO) to magnetically label bone marrow‐derived macrophages. The specific aim was to assess the intra‐carotid infusion route for bone marrow‐derived macrophage delivery at reperfusion. Fifteen Sprague–Dawley rats sustained 1 h of middle cerebral artery occlusion. USPIO‐labeled bone marrow‐derived macrophages were slowly injected for 5 min immediately after reperfusion in ischemic animals ( n = 7), 1 h after the end of surgery in sham animals ( n = 5) and very shortly after anesthesia in healthy animals ( n = 3). Multiparametric MRI was performed at day 0, just after cell administration, and repeated at day 1. Immunohistological analysis included Prussian blue for iron detection and rat endothelial cell antigen‐1 for endothelium visualization. Intra‐carotid cell delivery brought a large number of cells to the ipsilateral hemisphere of the brain, as seen on both MRI and immunohistology. However, it was associated with high mortality (50%). The study of sham animals demonstrated that intra‐carotid cell delivery could induce ischemic lesions and may thus favor additional brain damage. The present study highlights severe drawbacks to the intra‐carotid delivery of macrophages at the time of reperfusion in this rodent model of transient cerebral ischemia. Multiparametric MRI appears to be a method of choice to monitor longitudinally the effects of cell infusion, allowing the assessment of both cell fate with the help of magnetic labeling and of potential tissue damage. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Intra‐carotid cell delivery brings a large number of cells to the ipsilateral hemisphere of the brain following experimental stroke, but is associated with high mortality. In sham animals, intra‐carotid cell delivery induces ischemic lesions and may thus favor additional brain damage. Multiparametric MRI is a method of choice to monitor longitudinally the effects of cell infusion, allowing the assessment of both cell fate with the help of magnetic labeling and potential tissue damage.